Measures to Improve Zooveterinary Services on Livestock Farms and Locate Livestock (The Peerian Journal, 2022)
The article discusses the issues of landscaping around livestock, creating a quality fodder base, the construction of buildings, barns, veterinary and sanitary requirements for dairy cows